2011
DOI: 10.1002/ange.201101941
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Diboration Reaction by Activation of Diboron Compounds with Simple Lewis Bases

Abstract: Wechselnde Vorlieben: Durch die Wechselwirkung eines Tetraalkoxydiborans mit einer Lewis‐Base entsteht eine nukleophile Boryleinheit vom sp2‐Carbentyp, die nichtaktivierte CC‐Bindungen angreifen kann. Laut Computerstudien überlappt die stark polarisierte B‐B‐σ‐Bindung (HOMO) mit dem antibindenden π*‐Orbital (LUMO) der CC‐Bindung. Das normalerweise elektrophile Bor wird dabei nukleophil und zwingt das Olefin, sich wie ein Elektrophil zu verhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…When alkynylborane (11)w as subjected to the optimizedr eaction conditions for 4-vinylbiphenyl, 3a was not produced. [14] Then, bis(borylated) derivative ( 12)w as subjected to the reaction, without obtaining the 3a.T hese observations exclude the possibility that bis(borylated) or alkynylborane derivatives were intermediates in the alkynylboration of alkenes. [15] On the basis of these experiments, apossible reactionmechanism was proposed (Scheme 6).…”
mentioning
confidence: 99%
“…When alkynylborane (11)w as subjected to the optimizedr eaction conditions for 4-vinylbiphenyl, 3a was not produced. [14] Then, bis(borylated) derivative ( 12)w as subjected to the reaction, without obtaining the 3a.T hese observations exclude the possibility that bis(borylated) or alkynylborane derivatives were intermediates in the alkynylboration of alkenes. [15] On the basis of these experiments, apossible reactionmechanism was proposed (Scheme 6).…”
mentioning
confidence: 99%
“…CuBr, CuCl, Cu(OAc) 2 , CuO, and CuSO 4 were found to be efficient catalysts for the tandem C-S/C-N reactions, while CuI gave the best result (Table 1, entries 1-7). In view of recent advances in transition-metalfree reactions [4][5][6][7][8][9][10][11][12][13][14][15], we intentionally performed this reaction without any copper salt as catalyst, and we surprisingly found that the desired product was also obtained ( Table 1, entry 8). We then changed K 2 CO 3 to Na 2 CO 3 , but lower yield was encountered (Table 1, entry 9).…”
Section: Resultsmentioning
confidence: 94%
“…Early in 2001, Beller first reported a transition-metalfree intra-and intermolecular C-N coupling with aryl chlorides with primary and secondary amines as substrates [4]. Thereafter, a great number of C-X coupling reactions have been developed into transition-metal-free reactions [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…However, the progress in this field has opened a new window toward the activation of tetra(alkoxy) diboron compounds in a metal-free context by the formation of Lewis acid-base adducts [167][168][169][170][171][172][173][174][175] and their addition to unsaturated substrates can be performed with total chemo-, regio-, and stereoselectivity. Therefore, this historical prospection toward the activation of diboron has moved from direct reaction of Cl 2 B-BCl 2 with alkenes to the current methodology that circumvent the activation of tetra(alkoxy)diboron reagents with simple LBs.…”
Section: Discussionmentioning
confidence: 99%